Analisis Ikonologi Iklan Billboard Go-Pay di Yogyakarta - Arif Ardy Wibowo; Dinda Destiana Fahma Ayu (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2020)
Advertisement is one of the most well-known form of promotion, due to its broad reach as well as its ability to attract public attention, especially well- advertised products who popular among public. Billboard is one of the main from of outdoor advertising. Billboard is a poster in giant form. This giant poster designed to be seen by people who travel using vehicles with aim to introduce the brand of product. The purpose of this research is to explain the message or ideological meaning in “Go-Pay Billboard Advertisement”. In this research, the author used a qualitative descriptive study. The Go-Pay Billboard Advertisement in Yogyakarta is the main subject and main material to be studied and analyzed in this research. Meanwhile, the object of this research will be focused on the ideological meaning of the Go-Pay billboard advertisement in Yogyakarta using iconology analysis by Gillian Dyer. The data for this research are taken from observations and documentations. Based on the analysis that has been done, the author come to a conclusion that the ideological meaning of Go-Pay Billboard Advertisement is, easy, efficient and safe. Therefore, there are three things that the ads offered to public, such as, the convenience of making all kinds of payment, the efficiency (quick and easy), and security guarantee of every transactions, for all of the transactions are recorded in the secured system, moreover, to gain access to go-pay the customer must enter the password and OTP code send by Go-Jek through registered number. Thus, the customer does not need to be afraid losing the balance when they lost their mobile phone.